TINJAUAN HUKUM ISLAM TERHADAP PROSESI TRADISI UPACARA ADAT MA’BAKU-BAKU PADA MASYARAKAT URU (STUDI KASUS DESA LEDAN KECAMATAN BUNTU BATU KABUPATEN ENREKANG) - Arfan Halim; Patimah Patimah; Istiqomah Istiqomah (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The main problem in this research is how to review Islamic law on the traditional procession of the Ma'Mabku-Baku ceremony in the Uru community (Case Study of Ledan Village, Buntu Batu District, Enrekang Regency). The method used in this study is a descriptive qualitative method, namely in the form of field research. The data sources in this study are traditional leaders in Ledan Village, Buntu Batu District, Enrekang Regency as a community that still practices this custom. The results of this study indicate that the efforts made by traditional leaders and the local community who still carry out this tradition in this case: 1. Procession of the Ma'Baku-Baku Traditional Ceremony which is carried out once every three years for two days and also several rituals are carried out before it is carried out Ma'Baku-baku ceremonial traditions such as Ma'Paria and Ma'pole bubun, 2. Review of Islamic Law Against the Procession of the Ma'Baku-Baku Traditional Ceremony Tradition can be said not to be in conflict with Islamic law, let alone associating partners with Allah. The implication of this research is: for the people who still carry out the traditional Ma'Baku-Baku ceremony so that they continue to carry out this tradition, this tradition must be preserved because it is a legacy of ancient ancestors, but the Ma'Baku-Baku tradition must also be in accordance with Islamic teachings which was under the Prophet Muhammad saw so there is no element of polytheism.